Lowering Distribution Costs: The Key to Sustainable Health Development? - Webber, Cole (European Journal of Sustainable Development, 2021)
Recently selected as a winner of the government of Canada’s COVID-19: Digital clearinghouse challenge, our background work has uncovered that the cost of distribution can often be significantly higher than the cost of manufacture for high consumable medical supplies, like personal protective equipment (PPE). What’s worse, all of these costs are often not realized in suppliers’ pricing schedules, as further ‘hidden costs’ are incurred when governments procure centrally but use locally, demanding after the fact ‘sub distribution’. As the public and private sector alike look to rebuild stockpiles, how can we rethink the supply chain to maintain domestic production without simple subsidization? Conventionally, domestic suppliers have been unable to compete with overseas counterparts on price point. If distribution costs can be lowered, domestic supplies could become cheaper overall, more ethical and more sustainable. The key is in circumventing the architecture of a supply chain altogether — which is only as strong as its weakest link — and enabling an adaptive net that can match suppliers and distributors to orderers, enabling centralized procurement and direct, shortest path distribution at the same time. This strategy can improve the reliability, efficiency and resiliency of supply chains with impact on health costs.